Development and application of new diagnostic assays for the detection of prion proteins in transmissible spongiform encephalopathies - Ishii, Toru, author; Telling, Glenn, advisor; Liber, Howard, committee member; McGrath, Stephanie, committee member; Ross, Eric, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2018)
Transmissible spongiform encephalopathies (TSEs), well known as prion diseases, are fatal neurodegenerative disorders in humans and animals, which a prion protein (PrP) mainly implicates with the TSE pathogenesis. The normal cellular PrP isoform, referred to as PrPC, predominantly forms an α-helical structure. A structural alteration of the PrPC isoform can misfold into the infectious and pathogenic PrP isoform, referred to as PrPSc (or PrPD as disease-associated PrP). The PrPSc isoform consists of a β-sheet rich structure and accumulates in the central nervous system (CNS). The structural change and accumulation of this abnormal conformer alters physiochemical properties of the PrPC isoform. However, the conversional mechanism from PrPC to PrPSc isoforms is not clearly known. In general, the PrPC structure has two conserved Asparagine (N)-glycosylation sites that generate four various glycosidic forms (unglycosyl, two differing monoglycosyl and diglycosyl). In preliminary studies, TSE-disease mice exhibited the increased detection of under-glycosylated PrP forms, compared to controls. Although protein glycosylation plays various structural and functional roles, the importance of these glycans is not clarified in TSE pathogeneses. Recently, novel monoclonal antibodies (mAbs) against PrP molecules were reported. Of these mAbs, PRC7 mAb can recognize an unglycosyl form and one monoglycosyl form (mono-1) of PrP molecules specifically. In addition, PRC7 mAb has a unique feature to require denaturation and renaturation of PrP molecules to recognize PrPSc isoforms. Since PRC7 mAb cannot react with a diglycosyl PrP form that an abundance of normal PrPC isoforms express, PRC7 mAb preferentially detects PrPSc isoforms. Thus, these features of PRC7 mAb were applied to develop a sensitive enzyme-linked immunosorbent assay (ELISA) for the detection and quantification of under-glycosylated PrP forms in TSE-infected samples. My central hypothesis is that, the detection of under-glycosylated PrP forms is the hallmark of TSEs as diagnostic biomarkers for the disease progression. Here, I propose that loss of full glycosylation is implicated in the pathological mechanisms of TSEs. For instance, glycosylation is involved in the maintenance of protein structure. Thus, its modulation can initiate unstable conditions for maintaining proper PrPC conformations, which induce pathologic alterations of the PrPC structure. These aberrant formations could lead functional impairments of normal PrPC isoforms. In another aspect, the PrPSc isoform may lose glycans during the disease development of TSEs. Therefore, I assume that under-glycosylated PrP forms can be preferentially generated during the disease progression. To accomplish the proposed studies, I have developed two sensitive ELISA methods for the detection and quantification of PrP molecules in TSE-infected samples. Using the PRC7 and PRC5 mAbs as capture and detecting antibodies respectively, the 7-5 ELISA method specifically recognizes the certain under-glycosylated PrP forms that are significantly detected in TSE-infected materials. In addition, the D-5 ELISA method uses D18 anti-prion antibody as a capture antibody and has an exceptional capability to determine levels of only PrPC or total PrP molecules by different sample preparations. Using the D-5 ELISA method, I have detected the reduction of PrPC levels in TSE-infected materials at terminal stages, whereas total PrP levels were increased. These results were similar observations to a recent article using the conformation-dependent immunoassay. Since my protocols do not require a proteinase K (PK) reagent, these ELISA methods will be ultimately beneficial for TSE diagnoses, especially for detecting PK-sensitive PrPSc forms. Furthermore, the ELISA approaches would contribute to understand the TSE pathogenesis under the specific detections of PrPSc isoforms, based on glycosylated forms for distinguishing PrPC from PrPSc isoforms. This dissertation study will provide an innovative framework of the proposed projects that will achieve beneficial impacts into the fields of veterinary medicine, human medicine, and public health.
Keywords: glyocosylation; prion; monoclonal antibody; ELISA